2000
DOI: 10.1677/joe.0.1670447
|View full text |Cite
|
Sign up to set email alerts
|

Effects of estrogens and androgens on erythrocyte antioxidant superoxide dismutase, catalase and glutathione peroxidase activities during the menstrual cycle

Abstract: The effects of physiological changes in estrogens and androgens on the erythrocyte antioxidant superoxide dismutase, catalase and glutathione peroxidase enzyme activities during the menstrual cycle were investigated in healthy eumenorrheic women. Blood samples were taken on alternate days from twelve normally cyclic women (age range: 20 to 27 years; mean age: 24·1 years) from the first day of one menstrual cycle until the first day of the subsequent one. Plasma was analyzed for FSH, LH, estradiol, progesterone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
70
5

Year Published

2002
2002
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(81 citation statements)
references
References 29 publications
6
70
5
Order By: Relevance
“…Moreover, it was found that estrogen could enhance mitochondrial function resulting in the decreased reactive oxygen species production (Stirone et al, 2005). In addition, the enhanced GSH-Px and SOD were also observed (Massafra et al, 2000;Shahrokhi et al, 2012). Since estrogen can decrease the oxidative stress formation, therefore the reduction of MDA at 2-month intervention period might also be attributed to the decreased oxidative stress formation induced by estrogen.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, it was found that estrogen could enhance mitochondrial function resulting in the decreased reactive oxygen species production (Stirone et al, 2005). In addition, the enhanced GSH-Px and SOD were also observed (Massafra et al, 2000;Shahrokhi et al, 2012). Since estrogen can decrease the oxidative stress formation, therefore the reduction of MDA at 2-month intervention period might also be attributed to the decreased oxidative stress formation induced by estrogen.…”
Section: Discussionmentioning
confidence: 96%
“…A decrease of antioxidative conditions can also stem from an alteration of sex hormones during menopausal transition, and blood antioxidant capacity and antioxidant enzyme expression at a gene level were documented to positively correlate with E2 levels [16][17][18]. On the other hand, the association between (anti)oxidative stress-related markers and sex hormones has been still controversially reported; that is, urinary isoprostane excretion was not correlated with endogenous estrogen levels in perimenopausal women [19] or total antioxidant ability was not correlated with E2 levels during menopausal transition [20].…”
Section: Discussionmentioning
confidence: 99%
“…No significant effects of androgens were reported on antioxidant enzymes in erythrocytes [18]; conflicting results have also been reported about regulation of nitric oxide (NO) synthesis in immune system [19]; however antioxidant properties of testosterone in human neutrophils have been recently demonstrated, as indicated by suppression of superoxide anion and thiobarbituric acid-reactive substances (TBARS) levels, increase of NO levels, glutathione reductase activity and thiol groups; so testosterone administration at physiological concentrations had a greater antioxidant potential than higher concentrations [20].…”
Section: Discussionmentioning
confidence: 92%